2007
DOI: 10.1038/ng.2007.30
|View full text |Cite
|
Sign up to set email alerts
|

Widespread microRNA repression by Myc contributes to tumorigenesis

Abstract: The c-Myc oncogenic transcription factor (Myc) is pathologically activated in many human malignancies. Myc is known to directly upregulate a pro-tumorigenic group of microRNAs (miRNAs) known as the miR-17-92 cluster. Through the analysis of human and mouse models of B cell lymphoma, we show here that Myc regulates a much broader set of miRNAs than previously anticipated. Unexpectedly, the predominant consequence of activation of Myc is widespread repression of miRNA expression. Chromatin immunoprecipitation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

80
1,086
3
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,205 publications
(1,192 citation statements)
references
References 51 publications
80
1,086
3
6
Order By: Relevance
“…Whether and how c-myc and TCL1 cooperate toward the development of BL is, however, not known. A recent study with an inducible c-myc experimental system identified that it contributes to tumorigenicity by suppressing tumor suppressor miRs (Chang et al, 2008). Interestingly, a majority of those miRs repressed by c-myc, including miR-29b and miR-146a, were seen upregulated by LMP1 in our study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Whether and how c-myc and TCL1 cooperate toward the development of BL is, however, not known. A recent study with an inducible c-myc experimental system identified that it contributes to tumorigenicity by suppressing tumor suppressor miRs (Chang et al, 2008). Interestingly, a majority of those miRs repressed by c-myc, including miR-29b and miR-146a, were seen upregulated by LMP1 in our study.…”
Section: Discussionsupporting
confidence: 60%
“…In this study, we show that LMP1 can simultaneously induce several miRs with noted tumor inhibitory capacity and suppress tumor-promoting miRs (He et al, 2005;O'Donnell et al, 2005;Chang et al, 2008). Furthermore, we identified that LMP1, through its CTAR1 and CTAR2 domains, activates miR-29b expression to regulate TCL1 oncogene.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, we performed a pulse‐chase labeling experiment, which revealed a strongly enhanced TSC1 mRNA turnover in low MYC (+Tet) compared to high MYC (−Tet) P493‐6 cells (Fig 5C), indicating that MYC function stabilizes the TSC1 mRNA. Since MYC is a known regulator of microRNA (miRNA) expression (Chang et al , 2008), we examined whether the observed increase in mRNA turnover in response to MYC repression may be caused by miRNA regulation, which generally results in deadenylation and decay of target mRNAs. In search of potentially involved miRNAs, we identified conserved binding sites for the MYC‐suppressed miRNAs miR‐15a/16‐1, ‐22, ‐23ab ‐26ab, ‐29abc, ‐30e‐5p, and ‐195 in the 3′untranslated region (3′UTR) of the TSC1 mRNA by using the TargetScan algorithm (http://www.targetscan.org).…”
Section: Resultsmentioning
confidence: 99%
“…MiR‐15a and miR‐16‐1 have identical seed sequences and reside in the DLEU2 / miR‐15a/16‐1 cluster in the chromosomal region 13q14 whose deletion is commonly associated with the B‐cell malignancy chronic lymphocytic leukemia (B‐CLL; Klein et al , 2010). It was shown by others that MYC represses pri‐microRNA 15a/16‐1 transcription in P493‐6 cells through direct interaction with the pri‐microRNA promoter (Chang et al , 2008). Accordingly, we found that induction of MYC reduced miR‐15a levels in P493‐6 cells (Fig 5D).…”
Section: Resultsmentioning
confidence: 99%
“…The cooperating effects of MYC and BCL2 in lymphomagenesis have been shown in many studies. [4][5][6][7][8][9][10][11][12][13][14] Numerous case series of MYC/BCL2 double-hit lymphoma are reported in the literature. [15][16][17][18][19][20][21][22][23][24] MYC/ BCL2 DHLs represent B10% of all lymphomas that otherwise resemble diffuse large B-cell lymphoma (DLBCL).…”
mentioning
confidence: 99%